Hubungan Keaktifan Mengikuti Organisasi dengan Afeksi Positif Psikologis pada Mahasiswa Semester 6 Program Studi Kesehatan Masyarakat Fikkia Universitas Airlangga - Ardhya Farisha Martha (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
This study aims to analyze the relationship between organizational participation intensity and positive psychological affect among sixth-semester students of the Public Health Study Program, FIKKIA, Universitas Airlangga. Employing a quantitative correlational design, the research involved 36 respondents selected through purposive sampling using Slovin’s formula with a 10% margin of error. The instruments consisted of an organizational activity scale adapted from previous studies and the Affect Balance Scale (ABS) to measure positive affect, both of which demonstrated validity (r > 0.30) and high reliability (α > 0.7). Data were analyzed using the biserial correlation test. The results indicated that most students fell into the moderate participation category (44%), followed by high (36%) and low (20%) categories. Positive affect was reflected in five statements, including interest in learning new things, feeling pleased when opinions are heard, and pride in contributing to others. Negative affect appeared in four statements, such as frustration when performance is poorly evaluated and anxiety when speaking in public. The correlation analysis yielded a Sig. two-tailed value of 0.802 (>0.05), indicating no significant relationship between organizational participation intensity and positive psychological affect. These findings suggest the potential influence of confounding variables, such as personality traits, gratitude, social support, or academic workload, affecting both variables. The study highlights the importance of considering these factors in designing organizational activities to foster students’ psychological well-being.